OP0127 Identification of serological biomarker profiles associated with early response to tocilizumab in rheumatoid arthritis. (23rd January 2014) - Bay-Jensen, A.C.; Byrjalsen, I.; Kenwright, A.; Platt, A.; Karsdal, M.A.
Abstract : Background: RA characterized by poly-articular and synovial inflammation, cartilage loss and erosion of subchondral bone. It is critical to diagnose and effectively treat the disease early to suppress inflammation and prevent destruction of the joint. Thus, identification of the patients most likely to respond to a given intervention may be pursued for optimal benefits for both patients and payers. Objectives: To investigate early changes in biomarkers of bone, cartilage, synovium and inflammation as an effect of tocilizumab (TCZ) treatment, and to identify profiles associated with responders and non-responders. Methods: The LITHE study (Roche WA17823) is a 2-year phase III, 3-arm randomized, double-blind, placebo-controlled, parallel group, with moderate/severe active RA, inadequate response to MTX. 1196 patients were randomized to the 3 treatment groups: TCZ8mg/kg (TCZ8), TCZ4mg/kg or placebo. Every 4 weeks, patients received an infusion of TCZ8 mg/kg or 4mg/kg placebo for a total of up to 13 infusions in 52 weeks. Escape patients was defined as those who experienced <20% improvement in both swollen (SJC) and tender joint counts (TJC) at week 16. These patients were designated non-responders in current sub-study. The sub-study only the TCZ8 group was investigate and fasted serum was analyzed baseline and week 4weeks. Following biomarkers were measured: C2M (cartilage degradation), C3M (synovial inflammation), MMP3, total CRP, CRPM (MMP-degraded CRP), VICM (Citrullinated and MMP degraded Vimentin), ICTP (MMP destroyed type I collagen), osteocalcin (bone formation) and CTX-I (Bone resorption). The sub-study consisted of 102 responders and 33 non-responders. Data is shown as percentage change from baseline (Mann-Whitney test). Results: Cartilage degradation - C2M - was reduced to 90.4% of baseline levels upon treatment with TCZ8 in the responder group, whereas the level of C2M was increased to 111% of baseline level in the non-responder group (p=0.0031). Synovial tissue turnover, C3M, was decreased to 77.3% of baseline in the responder group, compared to 90.5% in the non-responder group (p=0.0034). MMP-3, ICTP and Citrullinated vimentin decreased to approx. 85% of baseline and there were no difference between the groups. The general inflammatory marker hsCRP was decreased in both responders and non-responders to approx. 35%, with no significant ability to separate these groups. In contrast, there was a significant difference between the level of MMP cleaved CRP, CRPM (p=0.031). The level of CRPM was decreased to 75.9% in the responder group and only to 85.9% in non-responder group. There were only minimal significant differences in the bone resorption and bone formation markers. Conclusions: The novel biomarkers of cartilage and synovial turnover were able to discriminate between responders and non-responders to IL-6 intervention, in contrast to traditional CRP and bone markers. Whether the markers may reflect the same response and power for prediction to other biological interventions need to be investigated. TCZ strongly inhibited cartilage degradation and inflammation mediated tissue turnover which may explain the clinical benefits of this biological intervention. Disclosure of Interest: None Declared